The development of instruments to measure the work disability assessment behaviour of insurance physicians - Anema Johannes R; Mulders Henny; Schellart Antonius JM; Steenbeek Romy; Kroneman Herman; Besseling Jan (BMC, 2011)
Abstract Background Variation in assessments is a universal given, and work disability assessments by insurance physicians are no exception. Little is known about the considerations and views of insurance physicians that may partly explain such variation. On the basis of the Attitude - Social norm - self Efficacy (ASE) model, we have developed measurement instruments for assessment behaviour and its determinants. Methods Based on theory and interviews with insurance physicians the questionnaire included blocks of items concerning background variables, intentions, attitudes, social norms, self-efficacy, knowledge, barriers and behaviour of the insurance physicians in relation to work disability assessment issues. The responses of 231 insurance physicians were suitable for further analysis. Factor analysis and reliability analysis were used to form scale variables and homogeneity analysis was used to form dimension variables. Thus, we included 169 of the 177 original items. Results Factor analysis and reliability analysis yielded 29 scales with sufficient reliability. Homogeneity analysis yielded 19 dimensions. Scales and dimensions fitted with the concepts of the ASE model. We slightly modified the ASE model by dividing behaviour into two blocks: behaviour that reflects the assessment process and behaviour that reflects assessment behaviour. The picture that emerged from the descriptive results was of a group of physicians who were motivated in their job and positive about the Dutch social security system in general. However, only half of them had a positive opinion about the Dutch Work and Income (Capacity for Work) Act (WIA). They also reported serious barriers, the most common of which was work pressure. Finally, 73% of the insurance physicians described the majority of their cases as 'difficult'. Conclusions The scales and dimensions developed appear to be valid and offer a promising basis for future research. The results suggest that the underlying ASE model, in modified form, is suitable for describing the assessment behaviour of insurance physicians and the determinants of this behaviour. The next step in this line of research should be to validate the model using structural equation modelling. Finally, the predictive value should be tested in relation to outcome measurements of work disability assessments.